Answer:
y=450+40x y=975-65x
Step-by-step explanation:
at five months they will have the same amount of money in their accounts
<h3>
Answer: 4 square inches</h3>
Explanation:
Square the linear scale factor to get 5^2 = 25
This means that,
new area = 25*(old area)
We take this idea in reverse to find the old area
old area = (new area)/25
old area = (100 sq inches)/25
old area = 4 square inches
Answer:
![A=189\ mm^2](https://tex.z-dn.net/?f=A%3D189%5C%20mm%5E2)
Step-by-step explanation:
<u>Surface Areas
</u>
Is the sum of all the lateral areas of a given solid. We need to compute the total surface area of the given prism. It has 5 sides, two of them are equal (top and bottom areas) and the rest are rectangles.
Computing the top and bottom areas. They form a right triangle whose legs are 4.5 mm and 6 mm. The area of both triangles is
![\displaystyle A_t=2*\frac{b.h}{2}=b.h=(4.5)(6)=27 mm^2](https://tex.z-dn.net/?f=%5Cdisplaystyle%20A_t%3D2%2A%5Cfrac%7Bb.h%7D%7B2%7D%3Db.h%3D%284.5%29%286%29%3D27%20mm%5E2)
The front area is a rectangle of dimensions 7.7 mm and 9 mm, thus
![A_f=b.h=(7.5)(9)=67.5 \ mm^2](https://tex.z-dn.net/?f=A_f%3Db.h%3D%287.5%29%289%29%3D67.5%20%5C%20mm%5E2)
The back left area is another rectangle of 4.5 mm by 9 mm
![A_l=b.h=(4.5)(9)=40.5 \ mm^2](https://tex.z-dn.net/?f=A_l%3Db.h%3D%284.5%29%289%29%3D40.5%20%20%5C%20mm%5E2)
Finally, the back right area is a rectangle of 6 mm by 9 mm
![A_r=b.h=(6)(9)=54 \ mm^2](https://tex.z-dn.net/?f=A_r%3Db.h%3D%286%29%289%29%3D54%20%5C%20mm%5E2)
Thus, the total surface area of the prism is
![A=A_t+A_f+A_l+A_r=27+67.5+40.5+54=189\ mm^2](https://tex.z-dn.net/?f=A%3DA_t%2BA_f%2BA_l%2BA_r%3D27%2B67.5%2B40.5%2B54%3D189%5C%20mm%5E2)
![\boxed{A=189\ mm^2}](https://tex.z-dn.net/?f=%5Cboxed%7BA%3D189%5C%20mm%5E2%7D)
Answer:
b
Step-by-step explanation:
Answer:
y = -16
Step-by-step explanation:
f(x)=3/4x+12 (replace f(x) with y)
y =3/4x+12 (rearrange to express x in terms of y)
y - 12=3/4 x
3/4 x = y - 12
3x = 4(y - 12)
x = (4/3)(y - 12)
x = (4/3)y - (4/3)(12)
x = (4/3)y - 16
(y) = (4/3)y - 16
(x) = (4/3)x - 16
comparing to general form
y = mx + b where b is the y-intercept
b = -16
Hence the y-intercept is y = -16